Mutations prevalent among rifampin- and isoniazid-resistant Mycobacterium tuberculosis isolates from a hospital in Vietnam. - Caws, M; Duy, P; Tho, D; Lan, N; Hoa, D; Farrar, J (2006)
Vietnam is ranked 13th among the WHO list of 22 high-burden countries, based upon estimated total number of tuberculosis cases. Despite having a model national tuberculosis program, consistently achieving and exceeding WHO targets for detection and cure, drug-resistant and multidrug-resistant tuberculosis cases continue to rise. Rapid multidrug-resistant tests applicable in this setting, coupled with effective treatment regimens, would be a useful tool in reversing this trend, allowing early identification of patients with multidrug-resistant tuberculosis and avoiding resistance-amplifying regimens. Sequencing of consecutive isolates identified by the National Tuberculosis Program showed 89% of isoniazid-resistant isolates could be detected by targeting just 2 codons, katG 315 and -15C-->T in the inhA promoter, while rifampin resistance will be more complex to detect, with many different mutation and insertion events in rpoB. The most prevalent rifampin resistance-conferring mutations, as in other countries, were in rpoB codons 531 (43%), 526 (31%), and 516 (15%). However, a hybridization-based resistance test with probes targeting the 5 most common mutations would only detect 78% of rifampin-resistant isolates. Overall, these data suggest that rifampin resistance may be used as a surrogate marker for multidrug-resistant tuberculosis and that a sensitivity of between 70 to 80% may be possible for rapid molecular detection of multidrug-resistant tuberculosis in this setting.